PENERAPAN PROGRAM FOS (FOLKTALE SPEAKING) SEBAGAI PEMBENTUK KARAKTER ANAK USIA DINI - Fitri Sundari; Ernata Sinaga; Nurmi Ritonga; Sulian Ekomila (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2017)
The age of children is the period that be view as an individu that begin to know their world. they not yet understand  so much thing about the value of life but they are so esasy to reserve immediately everything that surrounding gives to them without filter what the good thing and what the bad thing.This age is a period that the most appropriately for stimulating the development their personality. This jurnal dischus about stimulating the character of the clildren with folktale method. Foklore is a good methode that can be use to give value and moral education for the children. Folktale have so much education of moral value. But now foklore have no place anymore in heart of the children. Some Children thing that folktale is something that irrational so they can't accept it. Thats why to turn back the existence of the folktale, we must have the creative way to introduce it for the modern live of children. The author tries to get used to a program we call FOS (Folktale Speaking ) to rise the existence of the folktale Nusantara to form the character of the Chlidren.